Coupled Fractional Fourier Transform: Properties and Uncertainty Principle - Bahri, Mawardi (IndoMS, 2026)
The coupled fractional Fourier transform is a general form of the fractional Fourier transform. In the present work, we demonstrate basic properties of the proposed transformation, such as linearity, shifting and modulation. We also propose convolution and correlation theorems and then explore a generalized uncertainty principle for the coupled fractional Fourier transform. These crucial results are modifications of the corresponding properties pertaining to the fractional Fourier transform and the conventional Fourier transform.